Systematic Literature Review On Digital Marketing, E-Commerce, And Cultural Influence: Current Trends And Future Directions - Wiltri Oktaviani; Yulhendri Yulhendri (SAINTIS Publishing, 2025)
Information and communication technology has changed business significantly, with digital marketing and e-commerceas a key driver. Digital marketing uses the internet, mobile devices, and social media to promote products, enabling companies to reach a global audience cost-effectively E-commerce Facilitating online transactions, offering convenience and accessibility to global products. Culture plays a crucial role in influencing consumer behavior and marketing strategies. Local values, consumer preferences, and purchasing habits influence how products are selected, purchased, and used. This systematic literature review uses the PRISMA method to analyze articles from leading databases, addressing how cultural factors influence digital marketing strategies and e-commerce development in various global markets. The findings demonstrate a deep understanding of local and global cultural dynamics as key to effective marketing strategies. The study also identifies challenges and opportunities in digital marketing and e-commerce, including the need to build consumer trust and carefully manage personal data. Of the 36 articles that met the inclusion criteria, the study provides insights into current trends and future directions in digital marketing, e-commerce, and cultural influence.